Desenvolvimento local: a cadeia produtiva da banana em São João do Polêsine/RS - Rosso, Beatriz Deprá (2013)
The dynamics of space today, shows the competition between the different territorial units mediated by capital. This, in a way, confirms the importance of location and stimulus their crops in the process of regional participation making the living space attractive, by emphasizing their capabilities. In this perspective we intend to evaluate the cultivation of banana as an economic alternative to the local economy. In this perspective it is intended to evaluate the cultivation of banana as an economic alternative to the local economy.Thereby the general objective of the research focuses on characterizing and analyzing the the productive chain of banana in São João Do Polêsine/RS emphasizing their transformations (socio-economic, technological and cultural) responsible for (re) spatial organization and its insertion in the local / regional. Specifically, the research aims to: (a) identify the spatial transformations of banana production chain in São João Do Polêsine, (b) analyze the production chain that is organized for the development of banana, considering all its stages to the local market / regional and expanding agribusinesses and (c) verify that the banana is a local agricultural practice or whether it can be introduced in other municipalities that make up the MRG Restinga Seca. The investigative path to achieve the proposed objectives will rely on the dialectic method of investigation. The decision to work with this method is justified by the understanding of reality as a constantly changing process which is inserted in an environment of contrasts, contradictions and changes, where it is observed that different actors dialectical (re) configure the local space. In this way is intended to understand the dynamics of banana production chain and its influence on this territorial unit. It is understood, then, that the understanding of productive space pervades the practices of local society, which are directly linked through their work, in search of higher returns ie the insertion of new forms of agriculture in the local / regional economy. With this purpose looking up new alternatives in rural areas, to produce using all their potential locations.